Transatlantic Lessons on Higher Education Access and Completion Policy - Dougherty, Kevin J.; Callender, Claire (International Higher Education, 2018)
This article explores what England and the United States can learn from each other with regard to reducing social class and racial/ethnic differences in higher education access and completion. It focuses on seven policy strands: student information provision; outreach from higher education institutions; student financial aid; affirmative action or contextualization in higher education admissions; higher education efforts to improve retention and completion; performance funding; and degree of reliance on subbaccalaureate institutions.